2016
DOI: 10.1186/s12906-016-1144-7
|View full text |Cite|
|
Sign up to set email alerts
|

Herbal formula GAPT prevents beta amyloid deposition induced Ca2+/Calmodulin-dependent protein kinase II and Ca2+/Calmodulin-dependent protein phosphatase 2B imbalance in APPV717I mice

Abstract: BackgroundSynaptic dysfunction is one of the pathological characteristics of Alzheimer's disease (AD), which is directly related to the progressive decline of cognitive function. CaMKII and CaN have been found to play important roles in memory processes and synaptic transmission. So present study aimed to elucidate relationships between CaMKII, CaN and cognitive decline in APPV717I mice, and to reveal whether the cognitive improving effects of GAPT is conducted through rebalance CaMKII and CaN.MethodsThree-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Among them, GAPT, also called as GEPT or GETO in our previous papers, is a combination of herbal extracts and a patented Chinese herbal compound for AD. GAPT, composed of 4.4% ginsenoside from ginseng, 17.3% cistanche, 17.3% prepared Radix Rehmanniae, 13% processed Polygala tenuifolia , 13% Acorus gramineus , 13% Wide Radix Curcumae, 13% Poria cocos, and 9% Salvia officinalis (Shi et al, 2016; Tian et al, 2009), has been clinically widely used to improve learning and memory impairment. A single‐blind, randomized controlled clinical trial shows that 75 patients with suspected dementia were treated with GAPT for 3 months, and 1‐year follow‐up showed that GAPT can significantly improve the memory test scores compared with placebo group (Tian, Zhu, & Zhong, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, GAPT, also called as GEPT or GETO in our previous papers, is a combination of herbal extracts and a patented Chinese herbal compound for AD. GAPT, composed of 4.4% ginsenoside from ginseng, 17.3% cistanche, 17.3% prepared Radix Rehmanniae, 13% processed Polygala tenuifolia , 13% Acorus gramineus , 13% Wide Radix Curcumae, 13% Poria cocos, and 9% Salvia officinalis (Shi et al, 2016; Tian et al, 2009), has been clinically widely used to improve learning and memory impairment. A single‐blind, randomized controlled clinical trial shows that 75 patients with suspected dementia were treated with GAPT for 3 months, and 1‐year follow‐up showed that GAPT can significantly improve the memory test scores compared with placebo group (Tian, Zhu, & Zhong, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…GAPT, a mixed Chinese herbal extracts, has shown effectively decrease the level of GSK-3β expression and Aβ accumulation via the inhibition of γ-secretase (presenilin-1) and promoting insulin degrading enzyme (IDE) and neprilysin (NEP) in APPV717I transgenic mice [ 16 , 17 ]. Other possible mechanisms also have been explored [ 18 , 19 ]. Based on these previous studies, GRAPE granule with analogous activity and active components to GAPT may make additional benefits to AD patients with the treatment of donepezil or memantine.…”
Section: Discussionmentioning
confidence: 99%
“…The Editor has retracted this article [1]. Concerns were raised with a number of figures, specifically: Figure 1: the panels for Control, APP+D, APP+Gl and APP+Gh appear to be identical to the panels for Control, APP+D, APP+Gl and APP of Fig.…”
mentioning
confidence: 99%